Clinical presentation and management strategies of cardiovascular autonomic dysfunction following a COVID‐19 infection – A systematic review. (8th February 2023) - Reis Carneiro, Diogo; Rocha, Isabel; Habek, Mario; Helbok, Raimund; Sellner, Johann; Struhal, Walter; Wenning, Gregor; Fanciulli, Alessandra
Abstract: Background: Cardiovascular autonomic dysfunction may reportedly occur after a coronavirus‐disease‐2019 (COVID‐19) infection, but the available evidence is scattered. Here we sought to understand the acute and mid‐term effects of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection on cardiovascular autonomic function. Methods: We performed a systematic PubMed, Embase, Web of Science, medRxiv, and bioRxiv search for cases of cardiovascular autonomic dysfunction during an acute SARS‐CoV‐2 infection or post‐COVID‐19 condition. The clinical‐demographic characteristics of individuals in the acute versus post‐COVID‐19 phase were compared. Results: We screened 6470 titles and abstracts. Fifty‐four full‐length articles were included in the data synthesis. One‐hundred and thirty‐four cases were identified: 81 during the acute SARS‐CoV‐2 infection (24 thereof diagnosed by history) and 53 in the post‐COVID‐19 phase. Post‐COVID‐19 cases were younger than those with cardiovascular autonomic disturbances in the acute SARS‐CoV‐2 phase (42 vs. 51 years old, p = 0.002) and were more frequently women (68% vs. 49%, p = 0.034). Reflex syncope was the most common cardiovascular autonomic disorder in the acute phase ( p = 0.008) and postural orthostatic tachycardia syndrome (POTS) the most frequent diagnosis in individuals with post‐COVID‐19 orthostatic complaints ( p < 0.001). Full recovery was more frequent in individuals with acute versus post‐COVID‐19 onset of cardiovascular autonomic disturbances (43% vs. 15%, p = 0.002). Conclusions: There is evidence from the scientific literature about different types of cardiovascular autonomic dysfunction developing during and after COVID‐19. More data about the prevalence of autonomic disorders associated with a SARS‐CoV‐2 infection are needed to quantify its impact on human health.